Pesticide Effects on Nontarget Organisms - Frederick M. Fishel (EDIS, 2011)
Pesticides are an integral part of agriculture as Florida's climate fosters an environment conducive to major pest outbreaks throughout the entire year. Our environment also is favorable for the development and presence of beneficial organisms that positively affect our agricultural production and enhance our wildlife and plant communities. This revised 7-page guide addresses the effects of various types of pesticides on nontarget organisms, including natural enemies and beneficial organisms, such as honeybees, wildlife, fish, and nontarget plants. Written by Frederick M. Fishel and published by the UF Department of Agronomy, April 2011.